(untitled) (Bangladesh Journal of Livestock Research, 2020)
The study was designed to know the existing stocks under subsistence farming conditions to a specific area in Sylhet districts. Keeping this mind Bangladesh Livestock Research Institute initiated a baseline survey, awareness build-up through training programme and proper technical advisory services during July 2015 to June 2016 in Jaintapur and Balaganj upazilas under Sylhet district. For doing this, a total 200 respondents from two upazilas were randomly selected and interviewed face to face interview of every family in the village through pre-tested questionnaire for collection of information. A focus group discussion was also carried out to supplement the surveyed covering to assess the household asset possession, existing livestock production potentiality, available feed resources and disease prevalence situation as well as to find out the constraints prevailed at farmers level. After completing the base line survey, one hundred beneficiaries were selected randomly from two upazillas (50 from each upazilla) and were given training and demonstration of farm management activities and side by side proper technical advisory services also for creating awareness. The findings of baseline survey information indicated irrespective of the land, manpower, livestock resource and other input that are always being considered as social and economical up-liftman indicator for and specific area, the studied area is not exceptional. Any technology when introduce for specific area for specific purpose most of cases found remarkable improvement. So the scope and opportunity that is prevail in the studied area, being nourished through respective technological intervention for livestock development could be achieved. In this regard especially for livestock development, BLRI developed suitable technological intervention and awareness build-up programme is needed to a large area in different parts of the country to increase the overall existing livestock productivity to a great extent. Bangladesh J. of Livestock Res. 21-25: 56-64, 2018